Promising chitosan-alginate combination for rifampicin dry powder inhaler to target active and latent tuberculosis - Kurnia Sari Setio Putri, Laily Syahri Ramadhani, Theodora Rachel, Gatot Suhariyono, Silvia Surini (Journal of Applied Pharmaceutical Science, 2022)
A suitable excipient with certain characteristics is required in formulating a dry powder inhaler (DPI), to deliver the anti-tuberculosis (TB) drug into the lung and provide adequate drug concentration in the lung and in the alveolar macrophage, to overcome active and latent TB infection. This study aimed to explore the combination of chitosan and alginate in formulating rifampicin DPI. Rifampicin DPI was prepared by spray drying using various combinations of chitosan and alginate. The obtained rifampicin dry powder was characterized for its particle size distribution, morphology, moisture content, drug content, and entrapment efficiency. In addition to the dissolution study in a phosphate buffer of pH 7.4 with sodium lauryl sulfate 0.05% and in a phthalate buffer of pH 4.5, the cytotoxicity study toward cell line A549 was also conducted. The combination of chitosan and alginate in DPI F3 (RIF-Ch-Alg 2:1:1) provides a suitable drug release profile of rifampicin DPI in both simulated lung fluid (78.301% ± 1.332% in 2 hours) and simulated macrophage fluid (41.355% ± 1.259% in 2 hours). DPI F3 also possessed an aerodynamic particle size of 11.4288 ± 1.259 µm and was also considered safe toward pulmonary epithelial cells (viability 89.73%) in concentrations up to 0.1 mg/ml. In conclusion, combination of chitosan and alginate is a prospective carrier to develop dry powder inhaler with suitable characteristics for tuberculosis therapy.
Keywords: Rifampicin, dry powder inhaler, chitosan, alginate, drug release profile, cytotoxicity